Decreased Macular Retinal Thickness in Patients With Pterygium - Wang, Feng; Liu, Li Qi; Liang, Rong Bin; Zhang, Li Juan; Shu, Hui Ye; Liao, Xu Lin; Pan, Yi Cong; Wu, Jie Li; Su, Ting; Shao, Yi (Frontiers in Neurology, 2022)
Purpose: To explore alterations in macular retinal thickness (RT) and analyze correlation between macular RT and pterygium area, length in pterygium patients. Methods: Totally 13 patients with pterygium (left eye) and 13 healthy controls (left eye) were recruited. OCTA was applied to scan each eye to generate three-dimensional images. Based on the Early Treatment Diabetic Retinopathy Study (ETDRS) method, each image was divided into nine subregions for the ETDRS: central (C); inner superior(IS); outer superior (OS); inner nasal (IN); outer nasal (ON); inner inferior (II) ; outer inferior (OI); inner temporal (IT); and outer temporal (OT). The macular RT in each subregion was measured. Furthermore, the correlation between RT and the area, length of pterygium was analyzed. Results: A significant difference in visual acuity between the pterygium and control groups (P<0.05) was found. Besides, decreased intraretinal thickness of the IN and ON, increased intraretinal thickness of OT, decreased extraretinal thickness of OT, IN, ON, OS, and decreased retinal full layer thickness of medial superior, OS, IN, ON, and II subregions in pterygium group were observed. RT of the IN and ON subregions was negatively correlated with the length of pterygium (r =-0.5803 and -0.6013,P=0.0376 and P=0.0297). The thickness of the retina in the IN subregion was also negatively correlated with the area of retina (r = -0.5844,P=0.0359). In the ON subregion, the areas under the receiver operating characteristic (ROC) curve of the inner, outer RT and whole RT were 1.0 (95% confidence interval [CI]: 1.0), 0.882 (95% CI: 0.715 and 0.963), and 1.0 (95% CI: 1.0), respectively. The smallest area under the ROC curve of RT in the OT subregion was 0.018 (95% CI: 0–0.059). Conclusion: RT of pterygium patients was significantly decreased, and the main alterations occurred in the temporal side. suggesting there might exist retinal structural alterations in pterygium.